IMPLEMENTASI POJOK BACA DALAM MENGEMBANGKAN MINAT BACA SISWA SEKOLAH DASAR - Nisa, Azqiyatun; Toharudin, Moh; Sunarsiih, Diah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the reading corner in enhancing the reading interest of fifth-grade students at SD Negeri Sawojajar 03. The approach used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The subjects of this study are the teachers and fifth-grade students of SD Negeri Sawojajar 03. The study employs technique triangulation and source triangulation to ensure data validity. The results indicate that the implementation of the reading corner in improving students' reading interest is carried out in a structured manner through routine reading activities, the development of critical thinking skills toward reading materials, and the integration of the reading corner into classroom learning. The success of this implementation is supported by teacher role modeling, the availability of a variety of books, a comfortable environment, and an attractive reading corner design. However, several challenges remain in the implementation, such as the absence of reading desks, a lack of book collection updates, and the absence of recognition or rewards for students who actively engage in reading activities.